Spectro-temporal modulation detection and its relation to speech perception in children with auditory processing disorder. (April 2020) - Lotfi, Younes; Moossavi, Abdollah; Afshari, Parisa Jalilzadeh; Bakhshi, Enayatollah; Sadjedi, Hamed
Abstract: Objectives: Poor speech perception in noise is one of the most common complaints reported for children with auditory processing disorder (APD). APD is defined as a deficit in perceptual processing of acoustic information in the auditory system in which decreased spectro-temporal resolution may also contribute. Since the recognition of spoken message in the context of other sounds, is based on the processing of auditory spectro-temporal modulations, the assessment of spectro-temporal modulations sensitivity can evaluate the listener's ability to retrieve and integrate speech segments covered by noise. Therefore, the purpose of this study was to examine spectro-temporal modulation (STM) detection and its relation to speech perception in children with APD and to compare the results with aged-matched normally developed children. Methods: 35 children with APD and 32 normal hearing children (8–12 years old) were enrolled. In order to examine STM detection performance, six different STM stimulus conditions were employed using three different temporal modulation rates (4, 12 and 32 Hz) and two different spectral modulation densities (0.5 and 2.0 cycles/octave). Initially, the STM detection thresholds at these six STM stimulus conditions were measured in both groups and the results were compared. Thereafter, the relation between STM detection thresholds and speech perception tests, including consonant-vowel in noise and word in noise tests were assessed. Results: The STM sensitivity was poorer than normal for APD children at all STM stimulus conditions. Children with APD displayed significantly poorer STM detection thresholds than those of normally developed children ( p  < 0.05). Significant correlations were found between STM detection thresholds and speech perception in noise in both groups ( p  < 0.05). Conclusion: The results suggest that the altered encoding of spectro-temporal acoustic cues in the auditory nervous system may be one of the underlying factors of reduced STM detection performance in children with APD. The present study may suggest that poor ability to extract STM cues in children with APD, can be an underlying factor for their listening problems in noise and poor speech perception in challenging situations.